Hubungan Pengetahuan Dan Sikap Orang Tua Tentang Upaya Pencegahan Dengan Kejadian Demam Berdarah Dengue (Dbd) Pada Anak Di RSUD Banjarbaru Tahun 2015 - Ni Wayan Kurnia Widya Wati; Susi Astuti; Linda Kurnia Sari; STIKES Husada Borneo; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2016)
Dengue Hemorrhagic Fever (DHF) is the disease that is caused by dengue virus that infected through mosquito bite aedes aygypti. South Kalimantan is one of six provinces that has improvement of extraordinarily Dengue Hemorrhagic Fever (DHF). Dengue Hemorrhagic Fever (DHF) phenomenon in Banjarbaru city has upgraded in every year. Based on prevalensi data report, the rate of DHF in RSUD Banjarbaru has upgraded. In 2014, noted down 54 person who are victim of dengue hemorrhagic fever (DHF) and 1 person who is died. While, in the beginning 2015 (January-March) the victim of dengue hemorrhagic fever (DHF) is 153 person. The purpose of this research is to know the reletionship of parent’s knowledge and attitude about prevention efforts of Dengue Hemorrhagic Fever (DHF) phenomenon in children at RSUD Banjarbaru 2015. This research used analytic method and cross sectional approach. The population of the research is all parents whose their children have suffering of Dengue Hemorrhagic Fever (DHF) disease in kid room of RSUD Banjarbaru on April-June, 2015 totalled 66 person by taking the sample of 66 respondent. The instrument of this research is quesioner. The result of the research is knowed that parent’s knowledge is less 20 people (40,2%), enough 27 people (30,9%), and good 19 person (28,9%). Negative parents attitude is 45 people (68%) and positive attitude 21 people (32%). The positive rate of people who is suffering of DHF 45 people (61,9%) and negative DHF 21 people (32%). Based on chi square test there is the relationship beetwen parents knowledge and attitude about prevention efforts and dengue hemorrhagic fever (DHF) phenomenon of the children in RSUD Banjarbaru in 2015. By this research, the researcher hope to all family could be understand the way of dengue hemorrhagic fever (DHF) prevention, give the attention to residence area cleanliness and doing 3M+.